Effective Rates of Assistance for Norwegian Industries - Erling Holmøy; Torbjørn Hægeland (Statistics Norway, Research Department, 1995)
We measure the effective assistance to 17 Norwegian private industries in 1989 and 1991 caused by government budgetary subsidies, indirect commodity taxes, import protection through nominal tariffs and non-tariff barriers, and electricity market distortions. The assistance effects are measured by the change in the net-of-tax value added price due to a removal of the policy measures considered. Most industries were effectively assisted, but the effective assistance differs widely between industries indicating the overall distortive effect on the industry structure. Agriculture, Food Processing and Manufacture of Beverages and Tobacco stand out as the most assisted industries. Budgetary subsidies and non-tariff barriers had the strongest effective assistance effect.
Keywords: F13; H25; L60; L71; 330; Effective Rates of Assistance; Industrial Policy